1-Hydroxy Ethylidene 1,1-Diphosphonic Acid (HEDP) as a Corrosion Inhibitor for Aluminium - Hakeem, M.; Rajendran, S.; Regis, Peter Pascal (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
The present study is to use 1-hydroxy ethylidene 1, 1-diphosphonic acid (HEDP) as corrosion inhibitor for aluminium in aqueous solution containing 60 ppm Cl- ion was chosen as the inhibitor. Zn2+ is selected as the synergist, as Zn2+ ions in association with HEDP inhibitor is considered environmental friendly inhibitor for aluminium corrosion in alkaline (pH=11) media. The environment chosen is aqueous solution containing 60 ppm Cl- ions. To investigate the nature of the protective film, surface analytical techniques such as, Scanning Electron Microscopy (SEM), Atomic Force Microscopy (AFM) have been put to use in the present study. The formation of protective film has been confirmed using the electrochemical techniques such as polarization study and AC impedance spectral study. The above studies support the weight loss study.